Systematic Literature Review : UI/UX Design Methods for Government Applications - Rifqi Fahrudin; Petrus Sokibi; Ridho Taufiq Subagio; Irfan Dwiguna Sumitra; Irawan Afrianto; Estiko Rijanto (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2026)
Digital transformation in the public sector requires the implementation of user interface and user experience (UI/UX) design that ensures government services are effective, inclusive, and easy to use. However, numerous studies indicate that government applications continue to face challenges related to usability, accessibility, and misalignment between system design and user needs. This study aims to map UI/UX evaluation and design approaches in the context of government applications through a Systematic Literature Review (SLR) guided by the PRISMA framework. The literature search was conducted in the Scopus database using the keywords (“user interface” OR “user experience”) AND (“government application” OR “e-government”) AND (“method” OR “model” OR “framework”), resulting in 275 records. Following a rigorous screening and eligibility assessment, 10 articles met the inclusion criteria and were analyzed further. The findings indicate that the most commonly employed evaluation methods include Heuristic Evaluation, Cognitive Walkthrough, Usability Testing, and the Think-Aloud Protocol, while frequently used measurement instruments include the System Usability Scale (SUS) and ISO 25022/25023 standards. Recurrent issues identified across studies include non-intuitive navigation, limited system feedback, and accessibility barriers for users with special needs. This study highlights the importance of integrating expert-based and user-centered evaluations to enhance the quality of digital government services.